Positioning for regional anesthesia in femur fracture surgeries: how effective is femoral nerve block? a randomised control study - Purohit, Swetha; Ejjapuredi, Sireesha; Badami, Ramachandra N. (International Journal of Research in Medical Sciences, 2017)
Background: Fracture of the femur is a common orthopaedic problem following trauma in patients of all ages. This study was undertaken to evaluate the effectiveness of femoral nerve block (FNB) in positioning the patients for regional anesthesia. Methods: 100 patients between the ages 18 to 80 years, of ASA grade I, II and III, scheduled for elective surgeries of femur fracture were evaluated in 2 groups. Group FNB (n=50) received femoral nerve block with 15ml of 1.5% lignocaine and Group. Non FNB (n=50) was not given any block. Assessment of pain was carried out using visual analog scale (VAS). This was rated before, during and after the procedure of positioning for spinal/combined spinal epidural anesthesia (CSE). Vital parameters were tabulated. Results: VAS scores were noted at 0, 2, 5,10,15 minutes and at the time of positioning. VAS scores at 15 minutes after FNB was 1.473 ±0.1639 and 8.250±0.3615 in patients without FNB. Time taken for CSE was significantly less in FNB group (13.026±0.4628) minutes as compared to non FNB group (19.660 ±0.3742) minutes. Patient satisfaction scores were significantly higher in FNB group (45/50) 1.4952±0.033 as compared to non FNB group (10/50) 0.3460±0.1786. Quality of patient positioning was better in FNB group (2.782 ±0.1273) as compared to non FNB (1.382±0.2473). Conclusions:This study concludes that FNB is highly effective in giving good pain relief for positioning for regional anaesthetic procedures improving performance time and offers higher acceptance among patients with femoral fractures.